Comment on “Citrate adsorption can decrease soluble phosphate concentration in soils: Results of theoretical modelling” by Marek Duputel, Nicolas Devau, Michel Brossard, Benoît Jaillard, Davey L. Jones, Philippe Hinsinger and Frédéric Gérard (2013) - Gustafsson, Jon Petter; Lumsdon, David G. (Applied geochemistry, 2014)
By use of a multi-site surface complexation model, Duputel et al. (2013) showed that citrate can decrease the solubility of phosphorus in soils, in contrast to what is commonly expected. We have identified several major errors in their model, which put the conclusions in doubt. We argue that major re-evaluation of their modelling approach is needed.